Social Justice, Character Education, and Sport A Position Statement - Bredemeier, Brenda Light; Shields, David Light (2019)
In this article, we suggest that character education in sport contexts can promote social justice. After defining key terms, we suggest that rethinking competition and the nature of team relationships is required to build a team culture responsive to concerns for social justice. The character of the team provides a nexus within which to develop individual character, which is elaborated in terms of four types of character: moral, civic, intellectual, and performance character. To promote commitment to social justice, character educators can focus on three elements of moral character: moral reasoning, the circle of moral regard, and moral identity. Within civic character, three themes are elaborated: human dignity, full participation, and accountability. The dimensions of critical thinking, willful ignorance, and prioritizing the marginalized are discussed in relation to intellectual character. Performance character is discussed in relation to an ethic of excellence. Finally, conclusions for character educators are elaborated.
Keywords: Social Justice; Character; Competition; contesting theory; Moral Education